Transpiration Reduction in Maize (Zea mays L) in Response to Soil Drying - Hayat, Faisal; Ahmed, Mutez Ali; Zarebanadkouki, Mohsen; Javaux, Mathieu; Cai, Gaochao; Carminati, Andrea (Frontiers in Plant Science, 2020)
The relationship between leaf water potential, soil water potential and transpiration depends on soil and plant hydraulics and stomata regulation. Recent concepts of stomatal response to soil drying relate stomatal regulation to plant hydraulics, neglecting the loss of soil hydraulic conductance around the roots. Our objective was to measure the effect of soil drying on the soil-plant hydraulic conductance of maize and to test whether stomata regulation avoids a loss of soil-plant hydraulic conductance in drying soils. We combined a root pressure chamber, in which the soil-root system is pressurized to maintain the leaf xylem at atmospheric pressure, with sap flow sensors to measure transpiration rate. The method provides accurate and high temporal solution measurements of the relationship between transpiration rate and xylem tension. A simple soil-plant hydraulic model describing the flow of water across the soil, root and xylem was used to simulate the relation between leaf water potential and transpiration rate. The experiments were carried out with 5-week-old maize grown in cylinders of 9 cm diameter and 30 cm height filled with silty soil. The measurements were performed at four different soil water contents (WC). The results showed that the relation between transpiration and leaf water potential was linear in wet soils, but as the soil dried, the xylem tension increased, and non-linearities were observed at high transpiration rates. Nonlinearity in the relation between transpiration and leaf water potential indicated a decrease in the soil-plant hydraulic conductance, which was were explained by the loss of hydraulic conductivity around the roots. The hydraulic model well reproduced the observed leaf water potential. Parallel experiments performed with plants not being pressurized showed that plants closed stomata when the soil-plant hydraulic conductance decreased, maintaining the linearity between leaf water potential and transpiration rate. We conclude that stomata closure during soil drying is caused by the loss of soil hydraulic conductivity in a predictable way.